2013 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2013
DOI: 10.1109/ceidp.2013.6747067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gas heating and product molecules on discharge characteristics in dry-air-fed ozonizer

Abstract: Influences of gas heating and product molecules on discharge characteristics in dry-air-fed ozonizer was investigated. Especially, the dependence of gas temperature in streamer channel on occurrence frequency of streamer discharge was investigated in detail. In the experiment, repetitive positive or negative impulse streamer was generated respectively between needle-plane electrodes in synthetic air at atmospheric pressure. The repetition rate of the applied pulse voltage was controlled from 0.1 to 7.0 kilo-pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Therefore we selected these experimental conditions for the investigation reported here. It should be also noted that we confirmed that the transition to SFD with an increase of dischargerepetition rate occurs under different voltage conditions (dc, ac, impulse voltage with higher V p and lower f ), different gas conditions (synthetic air and room air, and so on), and different electrode configuration (gap distance, wireplane, and so on) [8][9][10][11]. The light emission from the impulse streamer discharge was observed using an ICCD camera (I) (Andor, iStar) and an image converter camera (TRW, MODEL 1D).…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…Therefore we selected these experimental conditions for the investigation reported here. It should be also noted that we confirmed that the transition to SFD with an increase of dischargerepetition rate occurs under different voltage conditions (dc, ac, impulse voltage with higher V p and lower f ), different gas conditions (synthetic air and room air, and so on), and different electrode configuration (gap distance, wireplane, and so on) [8][9][10][11]. The light emission from the impulse streamer discharge was observed using an ICCD camera (I) (Andor, iStar) and an image converter camera (TRW, MODEL 1D).…”
Section: Introductionsupporting
confidence: 52%
“…Discharge sources having a higher discharge repetition rate are now needed in many practical situations in order to increase the treatment throughput. In a previous investigation [8][9][10][11], we found a certain prebreakdown phenomenon which occurs just before positive dc sparkover in the case of a short nonuniform gap in air at atmospheric pressure, namely, a transition of a branched positive streamer to a single filamentary discharge (SFD) with increasing discharge-repetition rate. However, a decrease in treatment efficiency with increasing discharge repetition rates has been extensively reported in the literature [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations